What Do You See In The Cloud? Understanding the Cloud-Based User Experience through Practices - Tang, John; Brubaker, Jed R.; Marshall, Catherine C.; Marshall, Cathy (Human-Computer Interaction - INTERACT 2013, 2013)
End users have begun to incorporate cloud-based services into their collaborative practices. What spurs and constrains this adoption? Are the cloud services understood adequately and used effectively? How might we intervene to promote a better connection between user practices and cloud services? In this study, we focus on collaborative practices that surround the adoption, use, and understanding of two popular, but sometimes contrasting, cloud services for creating and sharing content: Dropbox and Google Docs. We conducted 22 in-depth interviews with people who used these services, including collaborators who used the services together, and people who had migrated from Google Docs to Google Drive. We found that users thought of the cloud in terms of the practices it helped them accomplish. Their understanding of the cloud was often shaped by the particular file storage and sharing technologies the cloud was re-placing (remediation). Furthermore, collaborating with others through the cloud sometimes revealed different assumptions about how the cloud worked, leading users to develop socially negotiated practices around their use of the cloud. We use this analysis to identify some specific opportunities for designers to help users build more accurate conceptual models of the cloud and use its capabili-ties more fully: (1) when users are adopting the cloud to enact a practice; (2) when users are replacing an existing technology with the cloud; and (3) when users are encountering others’ practices through collaboration.